Complementary unipolar duty cycle division multiplexing (CUDCDM) technique for wireless communications - Mohammadi, A.M.; Abdullah, M.K.; Mahdiraji, G.A.; Abas, A.F.; Mokhtar, M. (ACTA Press, 2008)
A new line encoding for duty cycle division multiplexing is proposed, under the name: Complementary unipolar Division Multiplexing (CUDCDM). The basic properties based on theoretical analysis as well as simulation studies have been done to evaluate the performance of this technique based on the signal energy and symbol error rate (SER). In this paper the performance of Complementary unipolar DCDM compared with unipolar DCDM as well as the time division multiplexing (TDM) techniques. The simulation has been set for wireless transmission based on free space propagation model with adaptive white Gaussian noise (AWGN). PSK and QAM are used as modulation schemes to evaluate these techniques against data rates. The study shows that the energy per bit in complementary unipolar DCDM, unlike that of TDM technique, increases with the number of users. The simulation result shows that complementary unipolar DCDM has better SER than TDM and unipolar DCDM, even in more distances.